Students’ Experience in Joining Merdeka Belajar-Kampus Merdeka Program - Ayustine, Regina Be; Dameria Magdalena Sidabalok (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
The experiences of students engaged in the Merdeka Belajar-Kampus Merdeka (MBKM) program under the English Education Study Program at FKIP Universitas Bandar Lampung are the main emphasis of this study. The main goal is to find out how these kids view and negotiate the program, which is meant to provide learning chances outside the conventional classroom setting, thereby improving both soft and hard abilities. Descriptive analysis was used in a qualitative research approach with which an in-depth knowledge of the experiences of the students could be obtained. Purposive sampling was used in the study to choose four students—one male and three female actively participating in the MBKM program. One month of observation and one-month of interviews comprised the data collecting process. Twice a week observations were undertaken, and students were free to carefully communicate their experiences thanks to WhatsApp interviews. According to the study, the MBKM program offers students useful chances for experiential learning, so promoting critical thinking, creativity, and useful skills development. Still highlighted, though, were difficulties with time management and adjusting to different learning contexts. The results imply that although the MBKM program has great potential to improve educational results, successful implementation of it depends on careful attention of students' requirements and limits